Big P Poetic Century. - Slow Reading Club ([S.l.] : Lulu, 2022)
Schlooz, Anna ; van der Ploeg, Anna ; Ringoet, Anouk ; Yassine, Asia ; Dhondt, Ellen ; Onghena, Emma ; Monteyne, Tosca
Big P Poetic Century was written collectively over 4 furious days in the spring of 2022, as part of a workshop by Slow Reading Club at KASK School of Arts, Ghent.
boek